Resting Hemodynamics and Response to Exercise Using the 6-Minute Walk Test in Late Pregnancy: An International Prospective Multicentre Study. Issue 1 (March 2020) - Dennis, A.T.; Salman, M.; Paxton, E.; Flint, M.; Leeton, L.; Roodt, F.; Yentis, S.; Dyer, R.A.
Abstract : ( Anesth Analg . 2019;129(2):450–457) The 6-Minute Walk Test (6MWT) is a validated tool that has been used to assess cardiorespiratory reserve in the nonpregnant population. Tools to identify pregnant women who have developed or are at risk of developing cardiac disease is lacking. Early recognition of cardiac disease and its risk in the pregnant population can reduce maternal morbidity and mortality as well as complications during and after birth. The aim of this study is to establish reference intervals for resting heart rate (HR) and the 6MWT in healthy women in late pregnancy, and to determine the expected and actual ratings of perceived exertion and breathlessness during exercise.